Quo Vadis: Pemberlakuan Undang – Undang Nomor 1 Tahun 2022 Terhadap Keberadaan Pajak Daerah Kota Padang - Fajri Kurniawan; Frenadin Adegustara; Gusminarti (Lareh Law Review, 2023)
The existence of financial relations between the central government and regional governments is an embodiment of the concept of delegating authority from the central government to regional governments which is referred to as "Regional Autonomy". Through the dynamics of central and regional government financial relations, a financial management system is required that regulates financial rights and obligations between the central government and regional governments that are carried out in a fair, transparent, accountable and aligned manner based on laws and regulations. The presence of Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments, is an improvement in the implementation of financial relations between the central government and regional governments as an effort to create an efficient allocation of national resources. So through this research the focus of the analysis on the two main pillars. First, how are the preparations for the implementation of Law Number 1 of 2022 on the Padang City Government in order to increase the regional tax sector? Second, what is the response of the Padang City Government to the implementation of tax options in Law Number 1 of 2022? To answer the focus of the study, this research uses empirical juridical research methods with research specifications to the Regional Revenue Agency of Padang City and is analyzed through library research and data analysis methods using juridical-qualitative. The results of this study conclude that the Municipal Government of Padang in preparation for the enactment of Law Number 1 of 2022 has carried out activities such as completing the drafting of the implementing Regional Regulations with the Provincial Government of West Sumatra, conducting regional potential studies with competent parties, conducting outreach to the public as taxpayers, and technical guidance to tax collector employees within the Regional Government Organization (OPD) in order to maximize the regional wealth potential in the City of Padang.